2021
DOI: 10.1002/jev2.12088
|View full text |Cite
|
Sign up to set email alerts
|

WNT3A‐loaded exosomes enable cartilage repair

Abstract: Cartilage defects repair poorly. Recent genetic studies suggest that WNT3a may contribute to cartilage regeneration, however the dense, avascular cartilage extracellular matrix limits its penetration and signalling to chondrocytes. Extracellular vesicles actively penetrate intact cartilage. This study investigates the effect of delivering WNT3a into large cartilage defects in vivo using exosomes as a delivery vehicle. Exosomes were purified by ultracentrifugation from conditioned medium of either L-cells overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
(66 reference statements)
0
24
0
Order By: Relevance
“…In in vivo experiments, Bertrand et al ( 35 ) came to the same conclusion that Wnt3a can modulate cartilage matrix maker genes (Sox9, Col2 and ACAN) through LRP6 phosphorylation and stabilization of β-catenin. In addition, Thomas et al ( 36 ) reported that Wnt3a-loaded exosomes can promote cartilage repair in the knees of mice. These exosomes may regulate circumarticular synovial tissues in addition to cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…In in vivo experiments, Bertrand et al ( 35 ) came to the same conclusion that Wnt3a can modulate cartilage matrix maker genes (Sox9, Col2 and ACAN) through LRP6 phosphorylation and stabilization of β-catenin. In addition, Thomas et al ( 36 ) reported that Wnt3a-loaded exosomes can promote cartilage repair in the knees of mice. These exosomes may regulate circumarticular synovial tissues in addition to cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…As WNT3a has a high affinity with exosomes, exosomes from L-cells (ATCC CRL2647/CRL2648; American Type Culture Collection, Manassas, VA, USA) were employed to deliver WNT3a to prolong the effect and were injected into mouse joints to repair large osteochondral defects. After 8 weeks, WNT3a-loaded MSC-Exos had successfully improved osteochondral defect repair via WNT signalling activation, while WNT3a without vehicle failed to activate WNT signalling to promote cartilage regeneration [ 56 ]. Overall, exosomes are potential vehicles with good cartilage penetration and cargo preservation, promising the delivery of proteins and small molecules, especially for hydrophobic substances.…”
Section: Exosome-based Strategies For Oamentioning
confidence: 99%
“…Due to this, the exosomes were administered weekly. Another study conducted by Thomas and colleagues was in favor of the use of semi-solid formulation to deliver the exosomes [193]. To demonstrate cartilage repair in C57BL/6 mice, exosomes were dispersed in liquid rat type I collagen gel.…”
Section: Direct Needle Injection: Exosome Gel and Formulationmentioning
confidence: 99%